(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Gender plays a significant role in shaping the food habits, nutrition levels, and overall health of individuals in Indian society. This paper explores the sociological implications of gender on food consumption, dietary practices, and nutritional outcomes. Drawing from various studies, reports, and data, it aims to unravel how gender norms, roles, and responsibilities impact access to food, distribution within households, and the consequent nutritional status of different genders. The paper highlights the structural inequalities that disproportionately affect women, particularly in rural and economically marginalized communities. Additionally, it addresses the intersections of caste, class, and rural-urban divides that compound the gender disparities in nutrition.